Determination of different organic contaminants in hard disk drive components / Lau Kean Yik - Lau, Kean Yik (2013)
The presence of organic contaminants in hard disk drive components is an issue as they may lead to drive operation failure. Various analytical instruments have been used to determine the organic contaminants. Determination of hydrocarbon contaminant in MBA and cover components was done by solvent extraction on the components, followed by GC-MS instrument analysis. For acrylate and methacrylate contaminant analysis, after sample collection through dynamic headspace sampling method, the extract was subjected to thermal desorption coupled with GC-MS. Hydrocarbon, acrylate, and methacrylate were quantified using internal standard technique, and recovery studied was carried out to assess the accuracy of the methods. Another organic contaminant, silicone, was also identified using ATR FT-IR technique. Silicone was determined at IR frequency region of 800 cm-1 with reference to a linear calibration curve obtained.